OBJECTIVE MODEL OF SOFTWARE STRUCTURE OF VIRTUAL LABORATORY IN SYSTEM THE KHERSON VIRTUAL UNIVERSITY - Kozlovskiy, Е.О.; Kravtsov, Г.М. (Journal of Information Technologies in Education (ITE), 2012)
Questions of designing, objective modelling of software structure and choice of technologies of virtual laboratory creation are considered. The virtual laboratory for economic disciplines in system of distance learning «Kherson virtual university» is considered.